2014
DOI: 10.1371/journal.pone.0100620
|View full text |Cite
|
Sign up to set email alerts
|

miR-365 Promotes Cutaneous Squamous Cell Carcinoma (CSCC) through Targeting Nuclear Factor I/B (NFIB)

Abstract: Aberrant expression of microRNAs plays vital roles in tumor development and progression. As transcription factors (TFs) are the critical components of signaling cascades, specific targeting effects of microRNAs to specific TFs may determine the role of microRNAs in different cancers. In this study, we identified Nuclear Factor I/B (NFIB) as one of the targets of miR-365 which was previously verified as an onco-miR in cutaneous squamous cell carcinoma (CSCC). Down-regulation of NFIB was a general feature in bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
72
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(72 citation statements)
references
References 29 publications
(52 reference statements)
0
72
0
Order By: Relevance
“…Through regulating the protein expression of their target genes, miRs participate in various cellular biological processes, including cell proliferation, apoptosis, migration, invasion and tumorigenesis (6)(7)(8). In recent years, certain miRs have been implicated in the development and malignant progression of CSCC (9,10). For instance, miR-365 serves a promoting role in CSCC through targeting nuclear factor I/B (9).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Through regulating the protein expression of their target genes, miRs participate in various cellular biological processes, including cell proliferation, apoptosis, migration, invasion and tumorigenesis (6)(7)(8). In recent years, certain miRs have been implicated in the development and malignant progression of CSCC (9,10). For instance, miR-365 serves a promoting role in CSCC through targeting nuclear factor I/B (9).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, certain miRs have been implicated in the development and malignant progression of CSCC (9,10). For instance, miR-365 serves a promoting role in CSCC through targeting nuclear factor I/B (9). In addition, miR-125b directly targets matrix metallopeptidase 13 and inhibits the CSCC cell proliferation, migration, and invasion (10).…”
Section: Introductionmentioning
confidence: 99%
“…Further study of this microRNA led to the identification of a downstream target of miR-365, nuclear factor I/B (NFIB) (Zhou et al, 2014). NFIB is a member of the nuclear factor I gene family in vertebrates and has been associated with a diverse set of transcriptional regulatory activities.…”
Section: Introductionmentioning
confidence: 99%
“…This repression affected downstream cancer-related effectors, including CDK6 (Zhou et al, 2014). Although the role of CDK6 in the initiation and development of tumors has been well-characterized (Kollmann et al, 2013), the underlying mechanism(s) responsible for the regulation of CDK6 by NFIB remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…However, cellular function and target genes of miRNAs has not been studied extensively in cutaneous squamous cell carcinoma (CSCC). Previous reports showed that miR-365 [4], miR-199a [5], miRNA-31 [6], miR-193b/365a [7], miRNA-361-5p [8], miR-124/-214 [9] and miRNA-125b [10] play important role in CSCC. miR-148a, a member of the miR-148/152 family, has been found to be downregulated in many types of cancer and its role in cutaneous squamous cell carcinoma remains unknown.…”
Section: A N U S C R I P Tmentioning
confidence: 99%